2010
DOI: 10.1103/physreva.82.012901
|View full text |Cite
|
Sign up to set email alerts
|

Reactive scattering ofH2from metal surfaces under fast-grazing-incidence conditions

Abstract: We have studied the interaction of molecular hydrogen with metal surfaces under fast-grazing-incidence conditions, by means of classical dynamics calculations based on density functional theory six-dimensional potential energy surfaces. We have performed calculations on two activated systems, H 2 /NiAl(110) and H 2 /Cu(111), and on two nonactivated systems, H 2 /Pd(111) and H 2 /Pd(110). We show that for rather open surfaces the computed 1 − R probabilities (where R represents the reflectivity) as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…44, this behavior has been observed for a variety of H 2 /metal surface systems, 243 from the activated to non-activated ones. Furthermore, these classical theoretical simulations have shown that the probability of dissociative scattering (the channel that is complementary to molecular reflectivity in fast grazing incidence (FGI) experiments) as a function of E n has a large resemblance to the dissociative adsorption probability obtained for thermal (and slightly above) energies at normal incidence.…”
Section: View Article Onlinementioning
confidence: 73%
See 2 more Smart Citations
“…44, this behavior has been observed for a variety of H 2 /metal surface systems, 243 from the activated to non-activated ones. Furthermore, these classical theoretical simulations have shown that the probability of dissociative scattering (the channel that is complementary to molecular reflectivity in fast grazing incidence (FGI) experiments) as a function of E n has a large resemblance to the dissociative adsorption probability obtained for thermal (and slightly above) energies at normal incidence.…”
Section: View Article Onlinementioning
confidence: 73%
“…Interesting predictions from the diffraction studies are that RID peaks should be larger than elastic diffraction peaks, 242 and that energy transfer to an intramolecular mode should be enhanced if the classical frequency corresponding to a specific rovibrational state is close to a nonlinear resonance condition. 243 This implies that experiments on dissociative scattering at FGI could be used to determine saturation values of dissociative chemisorption probabilities of highly activated systems like H 2 + Cu(111), Ag (111), and Au (111), which are not accessible in ordinary molecular beam experiments. 243 This implies that experiments on dissociative scattering at FGI could be used to determine saturation values of dissociative chemisorption probabilities of highly activated systems like H 2 + Cu(111), Ag (111), and Au (111), which are not accessible in ordinary molecular beam experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already discussed in the literature [2,8,11,12], the physical mechanism behind this phenomenon is the strong decoupling between the fast motion parallel to the surface, and the slow motion normal to it. Due to the grazing incidence conditions, the potential felt by the projectile is periodic (or quasi-periodic).…”
Section: Introductionmentioning
confidence: 93%
“…Beyond diffraction simulations, classical dynamics can also be used to study reactive scattering under fast grazing-incidence conditions. 197–199 These scattering simulations have shown that it is possible to determine sticking probabilities at thermal and quasi-thermal energies, from the threshold up to the saturation limit, by analysing molecular scattering under fast grazing incidence. Under these extreme conditions a molecule behaves much as it does under normal incidence and low incidence energy; that is, it can be reflected or dissociated.…”
Section: Grazing Incidence Fast Molecule Diffraction (Gifmd)mentioning
confidence: 99%